Exploring Students' Perceptions towards Higher-Order Thinking Skills in Vocational Training in Morocco - El Arfaoui, Imad; Anasse, Khadija (Journal of English Language Teaching and Applied Linguistics, 2026)
The cultivation of Higher-Order Thinking Skills (HOTS) in vocational and technical education has gained considerable priority, particularly given the rapid development of technology and the accelerating demand for non-routine cognitive competencies. Although Morocco has introduced national reforms that aim to embed analytical, evaluative, and creative dimensions within vocational programs, it remains necessary to understand how students perceive these initiatives and to what extent they experience HOTS being fostered during their training. The present study examines first-year students' perceptions of HOTS at OFPPT NTIC Rabat and employs a mixed-methods design combining a quantitative cross-sectional survey based on a Likert-scale questionnaire with qualitative open-ended responses. Forty-two first-year students enrolled in Information and Communication Technology programs participated in the study. Quantitative results indicate moderate HOTS-related conceptual understanding, with students demonstrating stronger awareness of the importance of HOTS for their future careers (M = 3.86) than of the specific cognitive processes involved (M = 3.07). Students also reported partial and inconsistent engagement in analysis- and problem-solving-based activities within their classrooms (M = 3.71 for critical-thinking prompts; M = 3.50 for problem-solving tasks). Qualitative findings reveal that approximately 70% of respondents were able to align their definitions of HOTS with Bloom's taxonomy cognitive levels of analysis, evaluation, and creation, while 20% were unable to provide a clear definition. Students further identified systemic barriers to HOTS development—notably time constraints, packed curricula, excessive rote memorization, and large class sizes. They recommended the integration of project-based learning, active methodologies, and professional teacher development as remedies. These findings highlight a meaningful gap between the national policy aspirations for HOTS integration and the actual classroom experiences of vocational learners, pointing to the urgent need for pedagogical reform within the OFPPT system.